Debating Igbo conversion to Christianity: a critical indigenous view - F. Hale (Acta Theologica)
Since the 1970s the dynamics of conversion have been a focal point of research with regard to the impact of Christianity on traditional African societies. Much of the scholarly debate about the matter has concentrated on West Africa. Such academic authorities as Elizabeth Isichei, Robin Horton, and Caroline Ifeka-Moller provided different theories about the relative importance of various factors. Within the genre of the novel, West African writers like the Ibgos Chinua Achebe, John Munonye, and T. Obinkaram added their voices to the debate through their fictional reconstructions of the confrontation of missionary Christianity and traditional cultures. That of Onuora Nzekwu is explored in this article.